Hybridisation and Lexical Variation: An In-depth Analysis of The Ministry of Utmost Happiness - Farwa Qazalbash; Humaira Irfan; Zehra Batool (Linguistics and Literature Review, 2023)
Hybridization and lexical variation are phenomena that are prevalent in many cultural domains, which as a process define the instances of hybridity in language and culture. The current study aims to investigate the variation English language in Arundhati Roy’s, The Ministry of Utmost Happiness to study the incorporation of code mixing between L1 (Hindi-Urdu) and L2 (English). This research also investigates how code-mixing results in lexical variation and hybridization in the context of South Asian languages. The findings of this research revealed that) the writer borrowed words, phrases, and sentences from both Hindi and Urdu languages to construct a specific form of hybrid identity. She frequently uses metaphorical language as an organism to convey its social and cultural backgrounds, indicating a linguistic hybridity submerged within a cultural context. Additionally, the findings also indicated that most of the borrowings stem from various sources, such as religion, cuisines, clothing, poetry, caste systems, and untranslatable expressions. Roy in particular resists translation of expressions, such as ‘Razai (Quilt), Masjid (Mosque), Baba (Father), and Inqilaab (Revolution) to create nuances of meaning embedded in the South Asian cultural context. Thus, the findings also revealed that the hybrid use of language by South Asian writers is in actual an attempt to reject the normative hegemony of Standard English and promote Hindi-English and Pakistani-English as an idea of celebrating hybrid identity.